Answer: The new amount is 0.78*5500. Which is 4290. The decrease is 5500-4290=1210.
2(x-6)=3(x+3)
Let's solve your equation step-by-step.
<span><span>2<span>(<span>x−6</span>)</span></span>=<span>3<span>(<span>x+3</span>)
</span></span></span>Step 1: Simplify both sides of the equation.
<span><span>2<span>(<span>x−6</span>)</span></span>=<span>3<span>(<span>x+3</span>)
</span></span></span><span>Simplify: (Show steps)
</span><span><span><span>2x</span>−12</span>=<span><span>3x</span>+9
</span></span>Step 2: Subtract 3x from both sides.
<span><span><span><span>2x</span>−12</span>−<span>3x</span></span>=<span><span><span>3x</span>+9</span>−<span>3x
</span></span></span><span><span><span>−x</span>−12</span>=9
</span>Step 3: Add 12 to both sides.
<span><span><span><span>−x</span>−12</span>+12</span>=<span>9+12
</span></span><span><span>−x</span>=21
</span>Step 4: Divide both sides by -1.
<span><span><span>−x/</span><span>−1</span></span>=<span>21/<span>−1
</span></span></span><span>x=<span>−21
</span></span>Answer:
<span>x=<span>−<span>21</span></span></span>
Answer:
The value of x that makes the equation equal to 0 is -2.
Step-by-step explanation:
In order to find this, we first must create the composite function using the designated operation. The operation is addition, so we just add them together.
f(x) + g(x) = (f+g)(x)
(x^2 - 2x) + (6x + 4) = (f+g)(x)
x^2 + 4x + 4 = (f+g)(x)
Now, in order to find when this is equal to 0, we need to factor.
x^2 + 4x + 4 = 0
(x + 2)(x + 2) = 0
When it is fully factored, we can set each parenthesis equal to 0 in order to find the value. Since the parenthesis are exactly the same, we only have to do this once.
x + 2 = 0
x = -2
So yuo simplyfly
15:20=3:4
6:8=3:4
8:12=2:3
9:12=3:4
so your answer is not c
The vertex angle is defined as the angle opposite the base. It can be calculated by formula, 180° - 2B = A where, B=base angle and A=vertex angle.
The two sides of an isosceles triangle are congruent, which means they are the same length. The third side of an isosceles triangle is larger than the other two and is known as the base.
Every triangle has three angles that add up to a total of 180°. The base angles are the two angles located along the base of isosceles triangles. In isosceles triangles, the base angles are always congruent, or equal.
The vertex angle is defined as the angle opposite the base. The vertex angle is always greater than the sum of the two base angles. The vertex angle is always calculated by subtracting the base angles from 180°, using the general formula: 180° - 2B = A, where B represents the base angle and A represents the vertex angle.
Thus, vertex angle is defined as the angle opposite the base.
To learn more about isosceles triangle refer here
brainly.com/question/18933031
#SPJ4